Imperio, constitución y diversidad en la América Hispana - Antonio Annino (Nuevo mundo - Mundos Nuevos, 2008)
This essay intends to show that the problems of governability of the newborn Hispano-American nations in the early 19th century, are not the result of a cultural incompatibility between Hispanic actors nor of the impact of liberal constitutionalism, but rather of a crisis of imperial nature that triggered convulsions throughout the territories of the Catholic Monarchy. The difference with other experiences in the Western World is that some characteristics of the Spanish Liberal Constitutionalism - applied in most of the American territories- and fundamentally in the continuity of Hispanic-colonial rule of justice. This explains the wide acceptance the latter legal system had by most local communities.